FORMATION OF THE MECHANISM FOR ATTRACTING FOREIGN INVESTMENTS - VASYLKIVSKYI, Dmytro; VYSHNIUK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive analysis of the theoretical and methodological foundations essential for the development of an effective mechanism to attract foreign investments, particularly in the context of the rapidly evolving global investment environment. It emphasizes the critical importance of adapting national investment strategies to align with ongoing global shifts, including changes in geopolitical dynamics, economic integration, and technological innovation. The study consolidates contemporary global investment trends and systematically identifies both the principal barriers and potential incentives influencing the flow of foreign direct investment (FDI) into economies undergoing structural transformation. Special attention is given to the specific challenges and opportunities present in transitional economies, with a focus on the role of institutional quality and regulatory stability. The article underscores the necessity for governments to adopt strategic, coordinated, and systemic policy measures aimed at increasing investment attractiveness, enhancing competitiveness, and removing administrative and institutional inefficiencies. A conceptual model of a comprehensive mechanism for attracting foreign investments is proposed, integrating six mutually reinforcing components: normative-legal, institutional, financial-economic, organizational-managerial, informational-analytical, and marketing. Each component is explored in detail, with a discussion of its role in fostering transparent investment frameworks, reducing investment-related risks, and providing sustained strategic support to investors across all stages of project development and implementation. Furthermore, the article highlights the wide-ranging positive impacts of increased FDI inflows, such as the modernization of national industries, job creation, the formation of regional innovation clusters, the adoption of advanced production technologies, and the enhancement of public revenues. In addition, the study draws on international best practices in investment policy formulation and underscores the importance of creating a predictable, resilient, and adaptable institutional environment, particularly in the context of Ukraine’s post-war reconstruction and economic recovery. The findings offer valuable insights for policymakers, practitioners, and scholars interested in fostering sustainable investment ecosystems.